The Teacher’s Creativity in Teaching Students in Baiturrahim Islamic Kindergarten Jambi - Mawaddah Warahmah; Wanti Hasmar (Indonesian Journal of Advanced Research, 2023)
Everyone basically has creativity with different levels. A person's creativity does not take place in a vacuum, but is preceded by the results of the creativity of those who worked previously. something new. In the development of the times, humans must be grateful to God who is creative because he has created humans who are so unique and creative. The teacher is a human figure who must be nurtured and imitated. As one element in the implementation of the education system in schools, teachers have a very important role in shaping, fostering and achieving educational outcomes. This role will certainly be felt when the teacher teaches in areas or villages that are far from the frenetic activities of humans, such as in cities. The role of the teacher is often the core resource in transforming the values ​​of science and other values ​​to students so that the abilities, knowledge, and skills of the teacher dominate the learning process and the formation of learning outcomes for their students. As an educator, teachers are required to be more creative in conveying messages and information in the learning process The teacher is a human figure who must be nurtured and imitated. As one element in the implementation of the education system in schools, teachers have a very important role in shaping, fostering and achieving educational outcomes. This role will certainly be felt when the teacher teaches in areas or villages that are far from the frenetic activities of humans, such as in cities. The role of the teacher is often the core source in transforming the values ​​of science and other values ​​to students so that the abilities, knowledge, and skills of the teacher dominate the learning process and the formation of learning outcomes for their students.